Pengaruh Pohon Literasi dan Outdoor Study dalam Pembelajaran IPAS Terhadap Literasi Sains bagi Siswa Kelas V di SD Terpadu Al-Qudwah - Luky Saputra; Amprasto; Noviana Mustapa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of literacy trees and outdoor study on elementary school students' scientific literacy. This type of research is an experimental study with a quantitative approach. The research design used is a one group pretest-posttest design. The population in this study were all grade V students of Al-Qudwah Integrated Elementary School, Lebak Regency, totaling 90 people who were divided into four classes, namely: 23 students in the control class (regular) in class V-B, 21 students in the experimental class-1 (literacy tree) in class V-A, 24 students in the experimental class-2 (outdoor study) in class V-C, and 22 students in the experimental class-3 (literacy tree and outdoor study) in class V-D. Determination of samples for each class was carried out using a saturated sampling method. The selection of experimental and control classes was carried out randomly. This study used a written test data collection technique in the form of a science literacy test sheet for science learning. The test sheet consisted of a pre-test and a post-test. Data analysis used t-test and ANOVA. The results of the study showed that there was an influence of literacy trees, outdoor study, and the interaction of literacy trees with outdoor study on scientific literacy in Grade V students of Al-Qudwah Integrated Elementary School. Of the four groups, the interaction of literacy trees and outdoor study provided a better influence, as shown by the results of the Games-Howel analysis with the Post Hoc test that the overall p-value was less than 0.05. The implication of this study is that through the use of appropriate media and learning methods, it will have a positive effect on students' scientific literacy abilities at school.